3D N, S-co-doped carbon nanotubes/graphene/MnS ternary hybrid derived from Hummers' method for highly efficient oxygen reduction reaction. (June 2020) - Chen, Yangyang; Xu, Chenxi; Hou, Zhaohui; Zhou, Minjie; He, Binhong; Wang, Wei; Ren, Wenqing; Liu, Yanping; Chen, Liang; Xu, Wenyuan
Abstract: Designing and preparing oxygen reduction reaction (ORR) catalysts with low cost, high activity and strong stability play a crucial function in the application of fuel cells and metal-air batteries. In this work, we use pristine graphite and carbon nanotubes (CNT) mixture as initial carbon source, and for the first time successfully prepare N, S-co-doped carbon nanotubes/graphene/MnS ternary hybrid (NSCNT/NSG/MnS) by modified Hummers' method followed by a pyrolysis process. The morphology, structure, composition and ORR performance of the obtained sample are measured by scanning electron microscope, X-ray diffraction and lots of other techniques. The results show that the successful synthesis of NSCNT/NSG/MnS is achieved by the combination of effective exploitation of residual Mn and S species and strong reducibility of carbon under high temperature. Besides, we find that the resultant NSCNT/NSG/MnS can not only effectively stabilize and disperse MnS nanoparticles, but also possess large specific surface area, high N content and unique 3D architecture. Compared to other counterparts, the obtained 3D NSCNT/NSG/MnS exhibits superior ORR performance (the onset potential moves positively to 1.00 V; limiting-current density achieves 4.93 mA/cm 2 ; ORR electron transfer number is close to four), which is proven to approach that of commercial Pt/C catalyst. Graphical abstract: Hummers' method derived 3D NSCNT/NSG/MnS ternary hybrid not only effectively stabilizes and disperses MnS nanoparticles, but also possesses large specific surface area, high N content and unique 3D architecture, thus leading to superior ORR performance. Image 1 Highlights: NSCNT/NSG/MnS hybrid was prepared by modified Hummers method followed by pyrolysis process. NSCNT/NSG/MnS hybrid had large specific surface area, high N content and 3D architecture. 3D NSCNT/NSG/MnS hybrid shows remarkable ORR performance.